Computer vision, imaging and computer graphics theory and applications : 11th International Joint Conference, VISIGRAPP 2016, Rome, Italy, February 27-29, 2016, Revised selected papers /: 11th International Joint Conference, VISIGRAPP 2016, Rome, Italy, February 27-29, 2016, Revised selected papers. (2017) - Unknown
No abstract available